International survey on training of dermatology residents in supportive oncodermatology: the RESCUE study - Ortiz Brugués, Ariadna; Fattore, Davide; Boileau, Marie; Forsea, Ana-Maria; Apalla, Zoe; Nikolaou, Vasiliki; Radević, Tatjana; Stojkovic-Filipovic, Jelena; Freites-Martinez, Azael; Kaminska-Winciorek, Grazyna; Elshot, Yannick; Baltas, Eszter; et al. (Supportive care in cancer, 2025)
The dermatological management of cancer patients with cutaneous adverse events occurring during and after oncologic treatment is known as supportive oncodermatology. This includes prevention, early identification, and mitigation of dermatologic toxicities. The aim of the international RESCUE (Residents’ survey on training of dermatology residents in supportive oncodermatology) study was to ascertain the current level of expertise in supportive oncodermatology among dermatology residents.